- cosθ ( secθ- cosθ)= sen²θ
sen²θ= cosθ ((1/cosθ)- cosθ)
sec²θ= 1- cos²θ
- sen θ / cos θ + cos θ / 1+ sen θ = sec θ
sec θ= ((1+sen θ)(senθ)+ cos²θ)/ (cosθ) (1+senθ)
secθ= (senθ+(sen²θ+cos²θ))/ (cosθ) (1+senθ)
secθ= (senθ+1) / (cos θ(1+sen θ))
secθ= (1) / (cosθ)
secθ= secθ
- (csc-cotθ)/(secθ-1)= cotθ
((1/senθ)-(cosθ/senθ))/((1/cosθ)-1)= cotθ
((1-cosθ/senθ))/((1-cosθ/cosθ))=cotθ
(1-cosθ/senθ) x (cosθ/1-cosθ)=cotθ
(cosθ)/(senθ)=cotθ
cotθ=cotθ
- ((cosθ)/(secθ))+((senθ)+(cscθ))=1
((cosθ)/(1/cosθ))+((senθ)/(1/cscθ))= 1
cos²θ+ sen ²θ= 1